Be cool: A review of hydro-physical changes and fish responses in winter in hydropower-regulated northern streams - Heggenes, Jan; Alfredsen, Knut; Bustos, Ana Adeva; Huusko, Ari; Stickler, Morten (Springer, 2018)
Winter is an ecologically challenging season for ectothermic cold-water fish in natural streams because of reduced flow and freezing. Hydropower regulation in many northern rivers increase winter stream flow and temperatures, and reduce ice formation and surface ice cover. From a background review of knowledge about e.g. Atlantic salmon (Salmo salar) and brown trout (Salmo trutta) winter survival strategies, we explore responses to hydropower impacts as a basis for adaptive management, mitigating strategies, and future research. Winter intensity and duration, hydrologic conditions and channel characteristics drive complex ice processes which become more complex and pervasive in smaller, high-gradient streams. Stream ice formation may be divided into the dynamic period ‘freeze-up’ in early winter with sub-surface ice, more stable ‘midwinter’ with surface ice, and the ecologically challenging ‘ice break-up’ in winter-spring with potential mechanical ice runs and scouring. The characteristics of periods vary depending on climate and hydropower regulation. In reaches downstream of power-plant outlets water temperature may increase and reduce surface ice formation. The mid-winter period destabilize or become absent. In bypass reaches flows decrease and facilitate freezing and ice production. Knowledge about longitudinal water temperature changes is limited. Hydro-peaked systems may aggravate high-low flow effects. A basic winter survival strategy in salmon and trout is energy storage, but also reduced metabolism, tolerance and starvation effected by quiescence. Energy storage may depend on local conditions, but there is little indication of adaptation to local thermal climates. Intraspecific phenotypic plasticity is important. The main behavioural strategy is risk-reducing sheltering in the substratum or deep areas, and nocturnal activity. Local movements between daytime refuges and nighttime slow-current activity areas are usually limited to meters. Larger fish may move more and aggregate in restricted suitable deep-slow refuge habitats such as pools and deep glides. Fish cope with ordinary thermal ice phenomena, and do not appear to become trapped in ice. Surface ice may reduce fish metabolism, but other factors, e.g. availability of substrate shelter, may override this effect. Mechanical ice break-ups and less surface ice may reduce survival. An adaptive mitigating strategy may be higher regulated flows in winter which increase rearing and/or resting habitat and survival, but studies are few and knowledge is limited. However, higher regulated flows also affect temperature regime. Low flows increase ice formation, reduce and fragment available habitat, and may reduce egg and fish survival. Influx of ground water may mitigate these impacts, as will stabilize minimum flows. Sudden drops in regulated water discharge should be avoided. Fish may strand, in particular at low temperatures in the daytime when fish are less mobile and seek shelter. The challenging winter season is understudied, and important management considerations and future research areas for better adaptive management are suggested.
Keywords: streams; winter ecology; regulation impacts; rivers; winter; ecology; salmon; trout; regulations